"I won't stay Indian, I'll keep studying" : race, place, and discrimination in a Costa Rican high school - Stocker, Karen (Book collections on Project MUSE., 2005)
"While teaching and researching on an indigenous reservation in Costa Rica, Karen Stocker discovered that for Native students who attended the predominantly racist high school outside the reservation, academic success and ethnic identity were inexorably intertwined in complex ways. At two extremes, students who maintained their indigenous identity despite pressures to disavow their culture did poorly in school, while others succeeded academically but rejected their Indianness and the reservation. In between those two poles, however, lay a whole host of multifaceted, less predictable responses. In "I Won't Stay Indian, I'll Keep studying," Stocker addresses the institutionalized barriers these students faced and explores the interaction between education and identity." ""I Won't Stay Indian, I'll Keep studying" documents how students from the reservation reacted to, coped with, and resisted discrimination."--Jacket.